2015
DOI: 10.3233/jad-141599
|View full text |Cite
|
Sign up to set email alerts
|

Development of an International Schedule for the Assessment and Staging of Care for Dementia

Abstract: The IDEAL schedule looks promising as tool for the clinical and social management of people with dementia globally, though further reliability and validity testing is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 25 publications
8
19
0
Order By: Relevance
“…The second correlation was higher than the first one mentioned above but with a difference of only 0.05, so the third hypothesis was not satisfied. Correlation between IDEAL‐P and CDR‐SB was very high ( r = 0.84, 95% CI = 0.73–0.90, n = 58), confirming the high correlation found earlier and supporting the construct validity of the original IDEAL‐P.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The second correlation was higher than the first one mentioned above but with a difference of only 0.05, so the third hypothesis was not satisfied. Correlation between IDEAL‐P and CDR‐SB was very high ( r = 0.84, 95% CI = 0.73–0.90, n = 58), confirming the high correlation found earlier and supporting the construct validity of the original IDEAL‐P.…”
Section: Resultssupporting
confidence: 82%
“…The sum scores of the IDEAL‐IC and the CDR‐SB show more overlap than expected because multiple items overlap on content, but the IDEAL‐IC still provides additional information on the care recipient's care needs on the individual items. In the article on the development of the IDEAL instrument, a high correlation with the CDR was found . The current study confirmed this with the CDR‐SB, supporting the validity of the original instrument.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It was in this setting that the IDEAL group decided to develop an easy‐to‐use, staging instrument that could be applied to guide the clinical and social care of patients . The IDEAL schedule fulfilled face and content validity criteria, had high inter‐rater reliability, and also satisfied preliminary evidence of concurrent validity against the CDR.…”
Section: Introductionmentioning
confidence: 99%